Virulence, ligninolytic enzymes and metabolic profile of Cryphonectria parasitica virulent and hypovirulent strains Converted by CHV1 hypovirus - Omar Abdelaziz Ouni; Lurdes Jorge; Luísa Moura; Valentim Coelho; Eugénia Gouveia (Instituto Politécnico de Viseu, 2020)
Introduction: Cryphonectria parasitica, the causal agent of chestnut blight, causes necrotic lesions (so-called cankers) on the bark of stems and branches of susceptible host trees. Cryphonectria hypovirus 1 (CHV1) infects C. parasitica and reduces the fungus virulence (hypovirulence) and alters the fungus morphology in culture (pigmentation and sporulation capacity). By these characteristics, the strains with hypovirus CHV1 are used in Europe as a biological control agent of chestnut blight. Objectives: The aim of this work is to understand the effect of hypovirus on fungi virulence by comparing the production of some lignin-degrading enzymes and the metabolic profiles of some isogenic virulent and hypovirulent (converted and original) strains. Methods: The virulence of each strain was evaluated by mycelial inoculation on apple fruits (cv. Golden Delicious) and on detached, one year old, chestnut branches. To detect the activity of ligninolytic enzymes (laccases, peroxidases and cellulases), various substrates and indicator compounds were used. The metabolic profile of C. parasitica was evaluated by the Biolog FF system using 95 different carbon sources. Results: Virulent strains were found to cause more significant necrotic lesions in chestnut branches (p<0.05) and to produce larger lignin-degrading enzymes. The use of Biolog FF MicroPlates indicated that the use of 95 carbon sources five isolates of C. parasitica were significantly different (p <0.001), when the substrates were grouped into six types of chemical compounds. The highest AWCD values were obtained for carbohydrates, carboxylic acids and polymers, and the lowest values for amines/amides, amino acids and miscellaneous. Conclusions: Virulence evaluation of C. parasitica strains is important to study the hypovirulence processes mediated by the hypovirus CHV1. The detached branches of chestnut were, in our study, more suitable than apple fruits test in discriminating hypovirulent from virulent strains of C. parasitica. Virulent strains showed higher activity of acid-tannic inducible laccase (Lac3) and other lignin-degrading enzymes (LiP, MnP, and cellulase) when compared with hypovirulent ones. The results of the metabolic profiles studies may lead to new perspectives for understanding the biological process used by the hypovirus therefore, this may suggest a method for discriminating hypovirulent strains and study ecology and field fitness in this fungal strains.